2016
DOI: 10.4312/dp.43.2
|View full text |Cite
|
Sign up to set email alerts
|

Ceramics among Eurasian hunter-gatherers: 32 000 years of ceramic technology use and the perception of containment

Abstract: We present two parallel and 32 000 years long trajectories of episodic ceramic technology use in Eurasian pre-Neolithic hunter-gatherer societies. In eastern, Asian trajectory the pottery was produced from the beginning. Ceramic figurines mark the western, European trajectory. The western predates the eastern for about eleven millennia. While ceramic cones and figurines first appeared in Central Europe at c. 31 000 cal BC the earliest vessels in eastern Asia was dated at c. 20 000 cal BC. We discuss women’s ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
2
0
1
Order By: Relevance
“…The introduction of ceramic technology, which is dated to the end of the Pleistocene, can be connected to changes in subsistence, a transition to a more sedentary way of life compared to the original Late Palaeolithic and Mesolithic lifestyles (Pavlů -Machová -Pchálková-Bártová 2019). In this way the appearance of pottery can be considered as the beginning of the Neolithic within the environment of hunter-fisher-gatherer communities (McKenzie 2010;Budja 2016). Part of these changes are big storage vessels, often sunk into the ground, which served to preserve food supplies in temporarily occupied places that were visited during the mobile life of the communities (Oshibkina /ed./ 1996, 6).…”
Section: Eastern Neolithicmentioning
confidence: 99%
“…The introduction of ceramic technology, which is dated to the end of the Pleistocene, can be connected to changes in subsistence, a transition to a more sedentary way of life compared to the original Late Palaeolithic and Mesolithic lifestyles (Pavlů -Machová -Pchálková-Bártová 2019). In this way the appearance of pottery can be considered as the beginning of the Neolithic within the environment of hunter-fisher-gatherer communities (McKenzie 2010;Budja 2016). Part of these changes are big storage vessels, often sunk into the ground, which served to preserve food supplies in temporarily occupied places that were visited during the mobile life of the communities (Oshibkina /ed./ 1996, 6).…”
Section: Eastern Neolithicmentioning
confidence: 99%
“…Tarihsel süreç içerisindeki kullanım alanlarına bakıldığında seramiğin sadece günlük kap-kacak kapları olarak kalmadığı, yapı malzemesi olarak tuğla ve kiremit, aydınlatma aracı olarak kandiller, takı ve süs eşyaları, dini ritüellerde ölü küllerinin muhafaza dildiği kaplar, figürinler ve lahitlerin yanı sıra çocuk oyuncaklarına kadar çok geniş bir alanda kullanıldığı görülmektedir (Budja, 2016;Hopper, 1986;Erman, 2012). En yaygın kullanım alanlarından biri olan kap-kacak seramikleri, çömlekler ve testiler dönemin şartlarına göre özellikle gıda maddelerinin depolanmasında kullanılan seramik eserler arasında yer almaktadır (Emre, 2023).…”
Section: Introductionunclassified
“…Recent archaeological research has demonstrated that the earliest pottery was already being produced by communities of hunter-gatherers in Asia (Chi 2002;Kuzmin 2002;2010;Bougard 2003;Keally et al 2004;Kuzmin, Vetrov 2007;Boaretto et al 2009;Wu et al 2012;Craig et al 2013;Budja 2016;Iizuka et al 2022a;2022b;Nakazawa et al 2022). Analysis of pottery dated to the very end of the Upper Palaeolithic has established that vessels discovered in Japan and Russia contain organic inclusions, deliberately added to the mixture, while the presence of quartzite -and occasionally also grog, or crushed recycled pottery -has been detected in pottery pastes from various parts of China (Chi 2002: 32-33;Keally et al 2004: 349).…”
Section: Introduction Clay Objects Containing Inclusions and Their Ch...mentioning
confidence: 99%